Sleep disordered breathing in patients with primary ciliary dyskinesia - KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA; GÖKDEMİR, YASEMİN (WILEY, 2013)
Background Upper airway manifestations of primary ciliary dyskinesia (PCD) can cause obstructive sleep apnea syndrome (OSAS). Also abnormalities of lung mechanics and gas exchange may lead to sleep abnormalities in these patients. Objectives To determine the rate of OSAS and sleep quality in PCD patients, and whether these are related to upper respiratory system manifestations and severity of lung disease in these patients. Methods Twenty-nine PCD patients and healthy controls were included to the study. Respiratory symptoms within the previous month were separately scored with the severity of the symptoms. Physical examination, pulmonary function tests, and ear-nose-throat assessments were obtained. All patients completed the Turkish version of Pittsburgh Sleep Quality Index (PSQI), sleep questionnaire, and underwent overnight polysomnography. Categorical variables were compared with chi-square and Fisher's exact test while continuous variables were compared with Student's t-test. Results Eleven PCD patients reported themselves to be poor sleepers, compared to only one subject in the control group (P=0.002). Sixty-five percent of PCD patients had habitual snoring (HS). Fifty-two percent of the PCD patients had OSAS in polysomnography. OSAS rate was higher in PCD patients who snored (P=0.008). HS and OSAS were more common in PCD patients who had cigarette smoke exposure in their homes (P<0.001 and P=0.02, respectively). Conclusions Patients with PCD have decreased sleep quality and higher rate of sleep disordered breathing compared to controls and higher rate of OSAS compared to population rates. Cigarette smoke exposure is an important risk factor for OSAS in PCD patients. Assessment and treatment of sleep disorders in PCD should be a part of disease management. Pediatr Pulmonol. 2013; 48:897-903. (c) 2012 Wiley Periodicals, Inc.
Keywords: sleep disordered breathing; primary ciliary dyskinesia; obstructive sleep; apnea syndrome; SECONDHAND SMOKE EXPOSURE; PRIMARY-SCHOOL CHILDREN; CYSTIC-FIBROSIS; APNEA SYNDROME; QUALITY INDEX; PREVALENCE; SYMPTOMS; RELIABILITY; DISTURBANCES; ASSOCIATIONS